Analysis and audit of key economic indicators of economic entities (a case study of the dairy industry) - Savchenko, Alla Mykolaivna; Saliamon-Mikhieieva, Kateryna Dmytrivna; Holynska, M. (Baltic journal Of economic Studies, 2018)
Instability of the environment and the lack of state support require economic entities to react instantly to its changes, only under such conditions the company will be able to survive and successfully operate in market relations. Economic and mathematical methods are an important tool for conducting qualitative analysis and audit, which enables to make well-grounded decisions. The purpose of the article is to study interrelation between the enterprise performance indicators, which are reflected in the enterprise financial statement, and factors of influence on the income from sales of products. The subject of the research is the theoretical and methodological basis of the use of mathematical modelling methods for the analysis and audit of key economic indicators of business entities on the example of the dairy industry. Methodology. To achieve this purpose, a system of general scientific and special methods is used. The research is carried out with the help of regression analysis, namely, the ridge regression, which distinguishes the influence of each factor in multicollinearity. Research results showed that among all factors, the greatest positive impact on the amount of revenue from sales belongs to the cost of production, indicating the rational use of resources, its increase leads to an increase in volumes of finished products, on which sales the company receives income. In the second place – the residual value of fixed assets, which characterizes their effective use in production activities. The third position is occupied by material costs. Practical implications. Accounts receivable has a negative impact and needs to be reviewed for its elimination and reduction. The volume of accounts receivable must correspond to the contractual discipline within the legal terms of the limitation period; only at such requirements, a positive effect on the financial status of the enterprise is possible. The problematic issue in the control over accounts receivable is the inability to receive transparent, relevant, and complete information about a business partner, which will be sufficient for conducting a qualitative analysis of settlements with debtors. This makes it impossible to predict the probability of the advent of the payment crisis of business entities, its prevention and elimination. Value/originality. The analysis and ranking of buyers, depending on the volume of purchases, the history of credit relations, and the proposed payment terms will increase the level of financial security of the enterprise; this measure will reduce the volume of bad debts. When entering into contracts of the purchase and sale of goods, works, and services, take into account the forecasts of cash receipts from debtors and prescribe penalties for considering the inflation component and taking into account the value of money in time. An increase in the number of customers of the enterprise products will reduce the risk of non-payment by one or more large customers. Consequently, the enterprise needs to update fixed assets and work to eliminate accounts receivable. Current liabilities have a negative impact, but their influence is negligible.

Нестабільність навколишнього середовища та відсутність державної підтримки вимагають від суб'єктів господарювання негайного реагування на його зміни, лише за таких умов компанія зможе вижити і успішно працювати в ринкових відносинах. Економічні та математичні методи є важливим інструментом для проведення якісного аналізу та аудиту, що дає змогу приймати обґрунтовані рішення. Метою статті є вивчення взаємозв'язку між показниками діяльності підприємства, які відображені у фінансовій звітності підприємства, та факторів впливу на дохід від реалізації продукції. Предметом дослідження є теоретико-методологічні засади використання методів математичного моделювання для аналізу та аудиту основних економічних показників суб'єктів господарювання на прикладі молочної промисловості. Методологія. Для досягнення цієї мети використовується система загальнонаукових і спеціальних методів. Дослідження проводиться за допомогою регресійного аналізу, а саме регресії гребеня, що відрізняє вплив кожного фактора на мультиколінеарність. Результати досліджень показали, що серед усіх факторів найбільший позитивний вплив на обсяг виручки від реалізації належить витратам виробництва, що свідчить про раціональне використання ресурсів, його збільшення призводить до збільшення обсягів готової продукції, на продаж якої компанія отримує дохід. На другому місці - залишкова вартість основних засобів, яка характеризує їх ефективне використання у виробничій діяльності. На третю позицію займають матеріальні витрати. Практичні наслідки. Дебіторська заборгованість має негативний вплив і потребує перегляду для її ліквідації та скорочення. Обсяг дебіторської заборгованості повинен відповідати договірній дисципліні в рамках правового терміну давності; лише за таких вимог можливий позитивний вплив на фінансовий стан підприємства. Проблемним питанням контролю за дебіторською заборгованістю є неможливість отримання прозорої, релевантної та повної інформації про ділового партнера, якої буде достатньо для проведення якісного аналізу розрахунків з дебіторами. Це робить неможливим прогнозування ймовірності настання платіжної кризи суб'єктів господарювання, її запобігання та ліквідації. Співвідношення / оригінальність. Аналіз і ранжування покупців залежно від обсягу закупівель, історії кредитних відносин, а також запропонованих умов оплати підвищать рівень фінансової безпеки підприємства; цей захід зменшить обсяг проблемної заборгованості. При укладанні договорів купівлі-продажу товарів, робіт і послуг враховують прогнози надходження грошових коштів від боржників і призначають штрафні санкції за розгляд інфляційної складової та з урахуванням вартості грошей у часі. Збільшення кількості клієнтів продуктів підприємства зменшить ризик неплатежів одним або кількома великими клієнтами. Отже, підприємству необхідно оновити основні засоби і працювати, щоб усунути дебіторську заборгованість. Поточні зобов'язання мають негативний вплив, але їхній вплив незначний.
Аналіз та аудит основних економічних показників суб'єктів господарювання (приклад дослідження молочної промисловості)
Keywords: analysis; audit; accounts receivable; financial statement of enterprise; regression model; аналіз; аудит; дебіторська заборгованість; фінансова звітність підприємства; регресійна модель